2000
DOI: 10.1046/j.1471-4159.2000.751310.x
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of Physiological and Behavioral Defects by a Slowpoke Ca2+ ‐Activated K+ Channel Transgene

Abstract: Abstract:The Drosophila slowpoke gene encodes a large conductance calcium-activated potassium channel used in neurons, muscle, and some epithelial cells. Tissuespecific transcriptional promoters and alternative mRNA splicing generate a large array of transcripts. These distinct transcripts are thought to tailor the properties of the channel to the requirements of the cell. Presumably, a single splice variant cannot satisfy the specific needs of all cell types. To test this, we examined whether a single slowpok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…RCK sites are proposed to mediate calcium's gating of the channel (Lee and Cui 2010;Yuan et al 2010), a modification that is common across species (Fodor and Aldrich 2009). Similarly, isoform-specific rescue of flight was shown in Drosophila (Brenner et al 2000). Across different species, age, cell type, and stress impact which isoforms of slo-1 are expressed (Tseng-Crank et al 1994;Xie and McCobb 1998;MacDonald et al 2006;Kim et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…RCK sites are proposed to mediate calcium's gating of the channel (Lee and Cui 2010;Yuan et al 2010), a modification that is common across species (Fodor and Aldrich 2009). Similarly, isoform-specific rescue of flight was shown in Drosophila (Brenner et al 2000). Across different species, age, cell type, and stress impact which isoforms of slo-1 are expressed (Tseng-Crank et al 1994;Xie and McCobb 1998;MacDonald et al 2006;Kim et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Channels encoded by the slo gene carry transient I KCa in muscles (Elkins, Ganetzky & Wu, 1986; Komatsu et al, 1990; Singh & Wu, 1989), and both transient and sustained I KCa in neurons (Saito & Wu, 1991). slo mutations in Drosophila cause action potential broadening (Atkinson et al, 1998; Brenner et al, 2000; Elkins & Ganetzky, 1988; Elkins, Ganetzky & Wu, 1986; Saito & Wu, 1991), decreased delay to first spike (Elkins & Ganetzky, 1988; Elkins, Ganetzky & Wu, 1986), increased interspike interval (Elkins & Ganetzky, 1988), changes in firing patterns that include “abnormal regenerative responses” (Saito & Wu, 1991; Singh & Wu, 1990), delayed repolarization of the neuromuscular junction (Gho & Ganetzky, 1992), and reduced synaptic transmission (Lee, Ueda & Wu, 2008; Warbington et al, 1996). Locomotor deficits are observed in adult slo mutants, including shaking under ether anesthesia, reduced flight, semi-paralysis in response to heat or bright light (Atkinson et al, 1998; Atkinson et al, 2000; Elkins, Ganetzky & Wu, 1986), and abnormal circadian patterns of activity (Ceriani et al, 2002; Fernández et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A null mutation in the slo locus strikingly alters the electrical properties of both neurons and muscles (22)(23)(24), affecting neurotransmitter release (25) and thereby causing a variety of behavioral defects among those in courtship behavior (26)(27)(28). We have previously demonstrated that a slo null mutant is behaviorally arrhythmic under free-running [constant darkness (DD)] conditions (13).…”
mentioning
confidence: 99%